Improved Split-GFP Systems for Visualizing Organelle Contact Sites in Yeast and Human Cells - Tashiro, Shinya; Kakimoto, Yuriko; Shinmyo, Manatsu; Fujimoto, Shintaro; Tamura, Yasushi (Frontiers in Cell and Developmental Biology, 2020)
Inter-organelle contact sites have attracted a lot of attention as functionally specialized regions that mediate the exchange of metabolites, including lipids and ions, between distinct organelles. However, studies on inter-organelle contact sites are at an early stage and it remains enigmatic what directly mediates the organelle-organelle interactions and how the number and degree of the contacts are regulated. As a first step to answer these questions, we previously developed split-GFP probes that could visualize and quantify multiple inter-organelle contact sites in the yeast and human cultured cells. However, the split-GFP probes possessed a disadvantage of inducing artificial connections between two different organelle membranes, especially when overexpressed. In the present study, we developed a way to express the split-GFP probes whose expressions remained at low levels, with minimal variations between different yeast cells. Besides, we constructed a HeLa cell line in which the expression of the split-GFP probes could be induced by the addition of doxycycline to minimize the artificial effects. The improved split-GFP systems may be faithful tools to quantify organelle contact sites and screen new factors involved in organelle-organelle tethering in yeast and mammalian cells.